El Desarrollo Cognitivo de los Niños de Cero a Tres Años del Centro Infantil “Nuevos Horizontes” desde el Enfoque Pedagógico Romántico. - Tituaña Sumbana, Liliana Marcela (2021)
This study aims “To strengthen the cognitive development of children from zero to three years of age at “Nuevos Horizontes” Children’s Center from the Romantic Pedagogical approach". The research is qualitative, non-experimental approach, the general methods used were induction-deduction; analysis-synthesis, and to gather the information the interview and observation were applied. The results of the methodological guide for the cognitive development of children from zero to three years of age from the romantic pedagogical approach contemplates 14 learning experiences of the four areas, three axes of development and learning. The implementation of the proposal improved in 94% the formative process in children from zero to three years of age at “Nuevos Horizontes” Children's Center. The proposal was validated by four users and three specialists who assigned 4.9 out of 5 points, which is very satisfactory.